Muscle fatigue and muscle soreness: etiology, mechanisms and prevention - Jasmina Pluncevic Gligoroska; Sanja Mancevska (Visoka škola za sport i zdravlje, 2021)
Muscle fatigue is a temporary and transient muscle incapacity to develop muscle power, and inability of muscle to perform work or maintain a certain level of physical activity. Several mechanisms are proposed as physiological base of the muscle fatigue: structural and functional changes that occurred in the sarcomera, reduced sarcoplasmic pH value, inhibition of the cross bridges cycle, blocking the process of excitation and contraction coupling, and depletion of energy reserves. Common consecutive process of muscle fatigue is muscle soreness. This phenomenon can lead to a disturbance of the integrity of muscle cells or temporary disruption of muscle function. Acute muscle soreness causes insignificant inconvenience in the athlete because it is short-term and quickly retreat. The delayed onset of muscle soreness (DOMS) often affect sport’s performance by limiting the range of motion, decreasing the muscle force and alternating the movement pattern. Recommendations for the prevention of muscle soreness include stretching exercises, gradually increasing of the training intensity and consumption of anti-inflammatory supplements. The scientific and empiric knowledge of the etiology and mechanisms of muscle fatigue and muscle soreness will allow better understanding how to alleviate and attenuate these adverse phenomena in athletes.
Keywords: muscle fatigue; muscle soreness; contraction; force